Resilience of the Tourism Sector during the Covid-19 Pandemic in Indonesia - Ni Wayan Marsha Satyarini; Andy Mulyana; Nadhira Hardiana; Noorina Hartati (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
Refocusing activities and reallocating the budget are the government’s strategies that make an impact on the tourism industry during the beginning of the Covid-19 pandemic. However, the income from dividends and Gross Domestic Product (GDP) of the tourism sector has decreased due to the Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar/PSBB), Enforcement of Restrictions on Community Activities (Pemberlakuan Pembatasan Kegiatan Masyarakat/PPKM), and travel restriction rules around the globe that have substantially reduced the number of visitors. Considering these challenges, in order to maintain the resilience of the tourist industry, a strategy is required, with limited income and government assistance. This research was conducted to examine the effects of refocusing activities and reallocating budgets of the tourism sector, as well as the resilience of the tourism sector on refocusing activities and reallocation budgets. This research belongs to an exploratory, descriptive, qualitative study. This study applies Miles and Huberman's theory for analyzing the data, which includes: 1) data reduction; 2) data display, and 3) conclusion drawing or verification. Focus group discussions (FGDs) were conducted. The FGDs were divided into two sections: 1) FGD with informants from the zoo and recreational park and 2) FGD with informants from government tourism offices. By refocusing activities and reallocating budgets, the tourism industry has shifted to the digital promotion and continues to raise awareness about tourism in various ways. When the tourism industry is making an effort to improve its resilience, there is a risk that some of the employees are laid off to ensure that the industry continues to be viable during the pandemic.